How a Simple Tort Claim is Transformed into an Exposition of the Implications of Artificial Intelligence on the American Legal System - Hunter, Richard J.; Shannon, John H. (Advances in Social Sciences Research Journal, 2023)
This article discusses issues relating to artificial intelligence (AI) in the context of a lawsuit essentially alleging negligence. The case, however, quickly turned to a discussion relating to how the plaintiff’s attorneys, with the aid of ChatGPT, fabricated as series of precedents that would have permitted their case to go forward on the basis of the application of a statute of limitations found in the Montreal Convention. The article discusses AI as it applies to the Rules of Professional Conduct and Rule 11 of the Federal Rule of Civil Procedure relating to the duties and responsibilities of attorneys. All of the quotations and factual representations are taken from the Case Documentations.